Construir el Estado, forjar una nación. La «nueva geografía» y su enseñanza en el Perú del Presidente Leguía (1919-1930) - Ombeline Dagicour (Caravelle)
The purpose of this paper is to analyze the contribution of geography teaching in Nation-state building in Peru during the Oncenio of President Augusto B. Leguía. This particular period proved to be a significant step toward centralized public schooling as well as for the circulation and appropriation in Peru of a “renewed or new geography” whose theoretical concepts and methodology had been strengthened since the end of the 19th century in Europe.